Lived experience-informed eating disorders research: an illustrative example. - Phillipou, Andrea; Calvert, Shannon; de Boer, Kathleen; Dwyer, Dominic; Eddy, Kamryn T.; Gao, Caroline; Pepin, Genevieve; Miles, Stephanie; Neill, Erica (Eating Disorders)
The mental health field, and more recently, the eating disorders field specifically, has witnessed a paradigm shift towards collaborative research which is conducted in partnership with individuals possessing lived and living experiences of mental health conditions (i.e. those with personal lived or living experience and those who are family, carers, or other supports). However, despite this shift, the challenge of engaging individuals with lived experiences in a manner that avoids tokenism, manages power imbalances, and ensures meaningful involvement persists. This paper aims to encourage those working in the eating disorders field to establish authentic, equitable partnerships with lived experience contributors. To provide clarity and to encourage researchers to engage in effective and authentic lived experience collaborations, this paper describes different types of lived experience involvement in research, using real-life examples from a study that is currently being established.